Unilateral torsion of fallopian tube at 32 of weeks of pregnancy followed by a normal delivery - Upadhyaya, Indira; Sharma, Richa (Nepal Journal of Obstetrics and Gynaecology, 2010)
A 24 year primi gravida at 32 weeks pregnancy presented with acute abdomen simulating torted ovarian tumor that underwent laparatomy/unilateral salpingectomy with the diagnosis of fallopian tube torsion is presented because of uneventful term vaginal delivery despite postoperative complication like gaped abdominal wound needing secondary suture. Keywords: acute abdomen in pregnancy; acute abdomen due to fallopian tube torsion. DOI: 10.3126/njog.v4i1.3336 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 58-59